2009
DOI: 10.1109/jsac.2009.090812
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of punctured rate-1/2 turbo codes exhibiting low error floors

Abstract: Abstract-The objective of this paper is two-fold. Initially, we present an analytic technique to rapidly evaluate an approximation to the union bound on the bit error probability of turbo codes. This technique exploits the most significant terms of the union bound, which can be calculated straightforwardly by considering the properties of the constituent convolutional encoders. Subsequently, we use the bound approximation to demonstrate that specific punctured rate-1/2 turbo codes can achieve a lower error flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…It can be predicted by the union bound estimate from the weight spectrum of the 1/2-code rate RCPT codes that, all PS-RCPT codes can obtain a lower error floor than the 1/3-code rate mother code within the high SNR region. The PRP-RCPT code with 66% systematic bit puncturing ratio (we consider this ratio since its distance spectrum is better than the PRP-RCPT code with 57.1%, as illustrated in Table 1) can achieve better error floor performance than the S-RCPT code, which complies with [8]. However, it can be observed that the performance of PRP-RCPT codes is obviously inferior to the OWSS-criterion based optimized PS-RCPT codes.…”
Section: Numerical Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…It can be predicted by the union bound estimate from the weight spectrum of the 1/2-code rate RCPT codes that, all PS-RCPT codes can obtain a lower error floor than the 1/3-code rate mother code within the high SNR region. The PRP-RCPT code with 66% systematic bit puncturing ratio (we consider this ratio since its distance spectrum is better than the PRP-RCPT code with 57.1%, as illustrated in Table 1) can achieve better error floor performance than the S-RCPT code, which complies with [8]. However, it can be observed that the performance of PRP-RCPT codes is obviously inferior to the OWSS-criterion based optimized PS-RCPT codes.…”
Section: Numerical Resultsmentioning
confidence: 89%
“…The code rates of all RCPT codes in Table 1 are fixed as 1/2, and influence of the systematic bit puncturing ratio N s /P (marked with "Ratio" in Table 1) is also presented. It can be seen that the OWSS criterion based PS-RCPT codes with sufficiently large information puncturing ratio (in this example, N s /P ≥ 25% ) have larger free distance than the PRP-RCPT codes with systematic bit puncturing ratio 57.1% and 66% (only these two systematic bit puncturing ratios are included here since only they are reported in [8]), which implies that the optimized OWSS criterion based PS-RCPT codes can achieve a lower error floor. Meanwhile, it can be observed that a larger information puncturing ratio is desirable for the PS-RCPT codes to realize a lower error floor performance.…”
Section: A Periodic Ps-rcpt Code Designmentioning
confidence: 96%
See 2 more Smart Citations
“…The first set comprises the two Maximum Free Distance (MFD) nonsystematic Viterbi codes (K = 7 and K = 9). The second set comprises the simulated floor regions of two modern punctured rate-1/2 Turbo codes [24] employing an interleaver size of 1000 bits, and after 8 decoding iterations. The specific codes used were a pseudo-randomly punctured Turbo code (PRP-PCCC) and a punctured systematic Turbo code (S-PCCC), both having a rate-1/3 PCCC(1,5/7,5/7) parent code.…”
Section: B Error Performance Simulation Results For (S-)cdo Codesmentioning
confidence: 99%